Roles of Vitamin E in Energy Metabolism During Neurite Outgrowth. (29th May 2020) - Stratton, Zachary; Davis, Abigail; Jonas, Elizabeth; Crowe-White, Kristi; Park, Han-A
Abstract: Objectives: Neurite outgrowth is a pivotal process of brain development and recovery after brain injury. This metabolically demanding process requires assembly of the cytoskeleton and formation and maintenance of synapses. We have recently found that treatment with alpha-tocotrienol, an antioxidant and a member of the vitamin E family, prevents loss of mitochondrial inner membrane potential during oxidative stress. In this study, we hypothesize that the mitochondrion is the central target of alpha-tocotrienol-mediated neuroprotection, and treatment with alpha-tocotrienol may improve neuronal energy metabolism and promote neurite outgrowth. Methods: Primary hippocampal neurons were grown in neurobasal media with or without alpha-tocotrienol for 3 weeks. Then, the morphological development of neurites, including polarity and arborization, was analyzed. We also assayed the ATP: ADP ratio in neurites using PercevalHR fluorescence biosensor after treatment with alpha-tocotrienol. Results: Neurons grown with alpha-tocotrienol achieved neuronal polarity prior to the control group, and alpha-tocotrienol treated neurons showed longer and more branched neurites compared to the control group. Treatment with alpha-tocotrienol enhanced ATP levels in primary hippocampal neurons. Conclusions: Our data show that alpha-tocotrienol improves mitochondria-mediated ATP production and supports the metabolically demanding process of neurite growth. This study also suggests that alpha-tocotrienol may be beneficial for recovery after brain injuries associated with neurite loss. Funding Sources: RG14811 (University of Alabama).